Estudo da eficiência da fotocatálise heterogênea com TiO2 no tratamento de líquidos percolados provenientes do aterro sanitário de Uberlândia-MG - Gonzaga, Kaio Augusto (2005)
Among the liquid residues of domestic origin, the leachate deserves special attention on the part of the organs of Environmental Legislation and of the whole community, for its high pollutant load and for its complex and variable composition. Thus, the main goal of this work was to evaluate the efficiency of the heterogeneous photocatalysis with TÍO2, in the treatment of leachate from the landfíll of Uberlândia - MG. The samples of the leachate were collected between may/2003 and april/2004. The characterization of the parameters indicated that the characteristics of the leachate change with the time, suffering alternation between the dry and rainy seasons. In the study of the photocatalytic treatment, 4 experimental designs were accomplished, to evaluating the influence of the variables pH, time of reaction (h), photocatalyst concentration (g/L) and air ílow (mL/s), and it answer variables were the percentile removal of DQO and the percentile removal of the concentration of nitrogen amoniacal. The results of the tests accomplished with these experimental designs indicated above the best leveis of the variables, in the studied experimental conditions. It was observed that the photocatalytic process with TÍO2, reached efficiencies of percentile removal of DQO of the order of 35%, being used 1,5 catalyst g/L, 2,0 mL/s of air, in pH same to 3,0 and with a time of reaction of 2,0 h. About of the percentile removal of the concentration of nitrogen amoniacal, the results were not so conclusive to the point to determine great leveis of the studied parameters. Besides, tests were accomplished being used the heterogeneous photocatalysis as secondary treatment, in the best conditions found in relation to the percentile removal of DQO. These tests were accomplished being used two different processes as pre-treatment, in the case the clarification and the floculation. The obtained results showed that these combined processes with the photocatalysis can be to reach effíciencies of percentile removal of DQO of the order of 45% for the clarification and 55% for the floculation.